Review of Level III Maternal Care in The Patients of Placenta Previa and Its Optimal Outcome: One-Year Experience at Combined Military Hospital Lahore - Sajjad, Rabia; Ashraf, Viqar; Ali, Chaudhry Amjad (Pakistan Armed Forces Medical Journal, 2022)
Objective: To review the cases of placenta previa with its optimal outcome, presented at Combined Military Hospital Lahore. Study Design: Cross sectional study. Place and Duration of Study: Department of Obstetrics and Gynaecology, Combined Military Hospital, Lahore Pakistan, from Jul 2018 to Jun 2019. Methodology: Total forty-six women, with singleton pregnancy and cephalic presentation were included. Women with placental abruption, having some local cause of antepartum haemorrhage, bleeding disorders, with severe medical disorder were excluded. Doppler ultrasound and MRI pelvis were performed to confirm the placenta previa and morbid adhered placenta (MAP). Results: Mean age of patients was 31.6 ± 3.5 years. Risk factors like previous scar and curettage was observed in 41 (89.1%) and 15(32.6%) patients respectively. On antenatal examination, placenta previa was diagnosed in 38 patients. Obstetrical hysterectomy was performed in 30 (65.2%) cases whereas lower segment caesarean was performed in 16 (34.7%) cases. Conclusion: Placenta previa is leading cause of maternal morbidity and mortality. Tremendous increase in the cesarean section rate is responsible for increased frequency of abnormally implanted placenta and such cases should be managed at tertiary care hospital to get optimal outcome.